Developing an Effective Character Education Model to Cultivate Noble Traits in Elementary School Students - Iman, Bagus Nurul; Setiana, Diana; Darmini, Mimin; Karim, Abdul (Universitas Pendidikan Indonesia, 2025)
The increasing involvement of youth in criminal activities is often linked to a lack of character development, highlighting the need for an effective educational approach. This study aims to develop a Character Education Model (CEM) along with a guidebook to enhance noble values such as honesty, responsibility, empathy, and respect among elementary school students. National character building is crucial, but youth criminal behavior is also related to insufficient parental attention. Therefore, schools must provide a child-friendly environment that offers a fun and challenging learning atmosphere to foster these core values. The development of this model is based on character education theories and frameworks emphasizing holistic moral development. The implementation of the IC learning plays a significant role by promoting student-centered learning and supporting both academic and social growth. This research employed a Research and Development (RD) design, including stages of planning, product development, field testing, revision, and final implementation. Data were collected through interviews and questionnaires involving 12 teachers and parents, and analyzed using descriptive qualitative methods. The validity of the CEM was confirmed by feedback from experts and practitioners. The results not only met the research objectives but also provided a theoretical foundation for character education models in elementary schools. This aligns with the goals of the Independent Curriculum to create a more personalized, flexible, and holistic approach to education. This study contributes a practical model for improving student character development in elementary education.